2006
DOI: 10.17221/3969-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The use of treated rape cake in a calf starter diet

Abstract: ABSTRACT:The objective of the experiment was to evaluate the effect of starter diet containing 10% of treated rape cake (TRC) with a reduced glucosinolate content on calf growth, development and health. The experiment included 45 calves allocated into 3 groups. After the colostrum period (5 days) the calves were fed 4 l of pooled fresh milk per calf/day and one of the starters ad libitum. The control group (S) was fed Standard starter with components with a standard nutrient content including fibre. Comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…in protein levels, and the reason for the decrease is due to the body's energy consumption at high levels for protein representation in the body. Gopfert et al (2006) showed no significant effect on the concentration of blood cholesterol when feeding hybrid calves on a starter pack containing soybeans or soybeans and 10% of grape damage. While Nasser et al (2013) noted a significant effect on the concentration of blood cholesterol when feeding on a starter pack containing soybean meal or soybean meal with dry Rumen contents of 8 16%.…”
Section: Effect Of Protein Sources On Physical Blood Parametersmentioning
confidence: 91%
“…in protein levels, and the reason for the decrease is due to the body's energy consumption at high levels for protein representation in the body. Gopfert et al (2006) showed no significant effect on the concentration of blood cholesterol when feeding hybrid calves on a starter pack containing soybeans or soybeans and 10% of grape damage. While Nasser et al (2013) noted a significant effect on the concentration of blood cholesterol when feeding on a starter pack containing soybean meal or soybean meal with dry Rumen contents of 8 16%.…”
Section: Effect Of Protein Sources On Physical Blood Parametersmentioning
confidence: 91%
“…The detailed information about the possible influence of rapeseed products, mostly seeds, is presented in Table S3, due to the large number of studies about these seeds and the relatively low significant impact of these products available in the modern human diet on thyroid function. In this comprehensive description, the results of the study on rapeseeds' impact on thyroid function in rats [82][83][84][85][86][87][88][89][90][91][92][93], dogs [94], cows [95][96][97], pigs and boars [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114], lambs [80,115], and goats [116] were described. Only one study that focused on the iodized rapeseed oil's impact on thyroid function in humans was found [27].…”
Section: Rapeseedmentioning
confidence: 99%
“…The introduction of rapeseed cake as part of the fodder has been largely studied. A lot of studies have been carried out and the results show that the introduction of rapeseed cake in little proportions in the fodder (until 10-15%) entails no significant changes in parameters such as nitrogen, lipid and mineral metabolism and also for the health status of the animals (Gopfert et al, 2006). Even in cow milk, no significant differences were found in fat, protein, casein, solids and non-solids fat content in the milk from cows fed with 15% of rape cake in fodder (Simek et al, 2000).…”
Section: Use Of Rapeseed Cake For Animal Feedingmentioning
confidence: 99%